Understanding the general practice nursing workforce in New Zealand: an overview of characteristics 2015-19 - Hewitt SL; Sheridan NF; Hoare K; Mills JE (CSIRO Publishing, 2021)
Limited knowledge about the nursing workforce in New Zealand general practice inhibits the optimal use of nurses in this increasingly complex setting. Using workforce survey data published biennially by the Nursing Council of New Zealand, this study describes the characteristics of nurses in general practice and contrasts them with the greater nursing workforce, including consideration of changes in the profiles between 2015 and 2019. The findings suggest the general practice nursing workforce is older, less diverse, more predominately New Zealand trained and very much more likely to work part-time than other nurses. There is evidence that nurses in general practice are increasingly primary health care focused, as they take on expanded roles and responsibilities. However, ambiguity about terminology and the inability to track individuals in the data are limitations of this study. Therefore, it was not possible to identify and describe cohorts of nurses in general practice by important characteristics, such as prescribing authority, regionality and rurality. A greater national focus on defining and tracking this pivotal workforce is called for to overcome role confusion and better facilitate the use of nursing scopes of practice.
Keywords: Adult; Aged; Female; General Practice; Humans; Male; Middle Aged; New Zealand; Nurse's Role; Nursing Staff; Primary Health Care; Surveys and Questionnaires; Workforce; health manpower; health personnel; nursing research; primary health care